If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 6y = 9 + 12y Solving 4 + 6y = 9 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 4 + 6y + -12y = 9 + 12y + -12y Combine like terms: 6y + -12y = -6y 4 + -6y = 9 + 12y + -12y Combine like terms: 12y + -12y = 0 4 + -6y = 9 + 0 4 + -6y = 9 Add '-4' to each side of the equation. 4 + -4 + -6y = 9 + -4 Combine like terms: 4 + -4 = 0 0 + -6y = 9 + -4 -6y = 9 + -4 Combine like terms: 9 + -4 = 5 -6y = 5 Divide each side by '-6'. y = -0.8333333333 Simplifying y = -0.8333333333
| 10x+4=2+18x | | 10a+7=11+3a | | 2+4z=14z+6 | | (14y+10)(13y+6)-(5y+2)(14y+10)=0 | | Y^4-14y+45=0 | | 5y+10x=55 | | N^3+6n^2=0 | | 10x+5y=55 | | 5x^2-25x^2+30x=0 | | 5x^3-25x^2=0 | | -8x^2=-72 | | 9y-12= | | 2x^2-7x=18 | | -x+2=x-4 | | 3x^2-8x=20+3x | | X^6-10x^5-400x^4+2500x^3=0 | | x^3-10x^2-400x+2500=0 | | 5x-(4-7x)-2=0 | | x^2+7x=-x | | -2(0.6)-1=y | | -2x-1=x-3 | | 0.5(-2)+2=y | | 0.5x+2=-x-1 | | bx^2=0 | | x^3+4x-32=0 | | 8n^2+7=-131 | | n+3/2=n-8/5+1 | | -3y-(5)=-11 | | 8x^2-3=797 | | 2(5)+y=12 | | Y+5/2y-7/3y=5/12 | | 3(-2)+y=-5 |